Niklas Luhmann's Theory of Politics and Law - King, M. author. aut Link
VI, 266 p.
Keywords: Niklas Luhmann's social theory stands in direct opposition to the dominant 'anthropocentric' traditions of legal and political analysis. King and Thornhill now offer the first comprehensive, critical examination of Luhmann's highly original theory of the operations of the legal and political systems. They describe how from the perspective of his 'sociological enlightenment' Luhmann continually calls to account the certainties, the ambitions and rational foundations of The Enlightenment and the idealized versions of law and politics which they have produced.